Chapter L'esperienza formativa di Anton Domenico Gabbiani a Venezia. Disegni e dipinti inediti - Morelli, Laura (Studi e saggi, 2020)
This paper aims to cast new light on Anton Domenico Gabbiani's first sojourn in Venice, which took place between 1678 and 1681, by following the two main biographies of the artist, written by Ignazio Enrico Hugford and Francesco Saverio Baldinucci, and by analysing new archival documents. Specific attention is given to the constant study of artworks by the great Venetian masters of the Sixteenth century, especially Titian, to whom Gabbiani devoted himself also in his later years, copying famous masterpieces of the Cadore painter. Through some unpublished drawings of the Uffizi and new or little-known paintings, the Venetian component of Gabbiani's style is identified in the way of composing and in the execution of airy and light figures. The highlights and intense Venetian colorism contributed to the creation of sophisticated chiaroscuro modulations expressed in the mimetic rendering of animals and landscape settings.